2007
DOI: 10.1101/gad.1519107
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA miR-124 antagonizes the anti-neural REST/SCP1 pathway during embryonic CNS development

Abstract: Neuronal gene expression is tightly regulated in developing CNS. Here, we demonstrate the anti-neural function of phosphatase SCP1 (small C-terminal domain phosphatase 1) during development. We further show that the neuron-enriched microRNA miR-124 directly targets SCP1-3 untranslated region (UTR) to suppress SCP1 expression. In developing spinal cord, expression of miR-124 and SCP1 is complementary, and miR-124 antagonism phenocopies SCP1 overexpression and vice versa. In P19 cells, miR-124 suppresses SCP1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
547
3
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 616 publications
(579 citation statements)
references
References 39 publications
21
547
3
8
Order By: Relevance
“…They found that the mRNA for the splicing factor PTBP1 is a direct target of miR-124 repression, and that part of the effects of miR-124 could be attributed to alternate mRNA splicing arising from the downregulation of PTBP1. Visvanathan et al [46] also reported that miR-124 function in the embryonic chicken neural tube promoted neuronal differentiation and cell cycle exit, while Krichevsky et al [45] found that coexpression of miR-124 and miR-9 in ES cells differentiated in vitro increased the fraction of neuronal cells. Previous studies demonstrated that miR-124 is likely to downregulate the level of numerous direct target mRNAs [41,42], as well as indirectly upregulate neuronal transcription by inhibition of the REST/NRSF transcriptional repressor complex [43,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the mRNA for the splicing factor PTBP1 is a direct target of miR-124 repression, and that part of the effects of miR-124 could be attributed to alternate mRNA splicing arising from the downregulation of PTBP1. Visvanathan et al [46] also reported that miR-124 function in the embryonic chicken neural tube promoted neuronal differentiation and cell cycle exit, while Krichevsky et al [45] found that coexpression of miR-124 and miR-9 in ES cells differentiated in vitro increased the fraction of neuronal cells. Previous studies demonstrated that miR-124 is likely to downregulate the level of numerous direct target mRNAs [41,42], as well as indirectly upregulate neuronal transcription by inhibition of the REST/NRSF transcriptional repressor complex [43,46].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-124 appears in part to mediate the repression of non-neuronal genes in neurons [41][42][43], as well as the downregulation of genes expressed in neural progenitors [44]. Overexpression of miR-124 (and other brain-enriched miRNAs) in mouse embryonic stem cells promotes neuronal fates [45], and a recent study indicates that miR-124 can promote neuronal differentiation via inhibition of the Ctdsp1/SCP1 phosphatase, a component of the REST/NRSF transcriptional repression complex [46]. miR-124 can also target PTBP1, a global repressor of alternative splicing, thereby regulating alternative splicing during neuronal differentiation [47].…”
Section: Introductionmentioning
confidence: 99%
“…It is highly likely that this circuitry is disrupted in cancer differentiating neurons. 55 SCP1 is an antineural factor that acts as a part of the REST complex to prevent the expression of neural genes in nonneural tissues. 56 This results in the establishment of a double-negative feedback loop between miR-124 and the REST complex.…”
Section: Micrornas In Glioblastomamentioning
confidence: 99%
“…But miR-124 expression is absent in non-neuronal cells, even neuronal progenitor cells. A negative feedback loop operates between miR-124 and SCP1/REST pathway that decides neural or anti-neural behavior of the cell [10,11].…”
Section: Introductionmentioning
confidence: 99%